Pepe Boyolali River: Analysis of Water Quality Using the Pollution Index Method - Frista Ananda Rizky; Hashfi Hawali Abdul Matin (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2023)
This study uses the pollutant index method to determine the form of river utilization by the surrounding community and the level of river water pollution. The research method used in this study is qualitative and quantitative analysis. Qualitative descriptive analysis method is used to analyze the form of river utilization by the community. Analysis of river water quality used quantitative method which refers to the Decree of the Minister of Environment 115/2003 concerning Determination of Water Quality Status using the Pollution Index (PI) method. The results of the analysis show that the community uses the Pepe River as a source of water and rainwater storage, waste disposal sites, fishing grounds, drainage channels, and agricultural irrigation. So that it has the potential to experience water pollution due to the entry of domestic-industrial waste. Based on PI, the flow of the Pepe River is proven to be lightly polluted, with the results of several parameter measurements showing results above the quality standard. Therefore, one of the recommendations that can be applied to overcome these problems is to develop the concept of Community-Based Development by involving the active role of all society levels in planning and implementing river management and development activities.